Factors Affecting Waiting Time for Completion of BPJS Patient Administration - Meliala, Sri Agustina; Nur, Fauziah; Marliani Lase, Ester (Jurnal Perilaku Kesehatan Terpadu, 2023)
Waiting time is the grace period when the patient is allowed to go home by the doctor in charge of the patient until they leave the hospital. Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 129 of 2008 concerning Minimum Service Standards for Hospitals, it is stated that the standard waiting time for repatriation patients is not more than 2 hours. This study aimed to determine the factors that affect the waiting time in completing the administration of repatriation of BPJS inpatients at Mitra Medika Hospital Tanjung Mulia in 2022. This is quantitative research with a cross sectional approach. The population in this study was all inpatient nurses’ amount 93 people. The sample in this study was the entire population of inpatient nurses. The data analysis technique was done by using univariate and bivariate analysis. The results showed that there was an influence of human resources with waiting time for discharge of patients with p-value 0.009 < 0.05, Administration with waiting time for discharge of patients with p-value 0.005 < 0.05, Facilities and Infrastructure with waiting time for discharge of patients with p -value 0.007 < 0.05. The conclusion shows that there is an effect of waiting time for discharge of patients with human resources, administration, and facilities and infrastructure at Mitra Medika Hospital Tanjung Mulia. It is expected that the hospital provides routine programs to improve the skills and abilities of nurses in completing the repatriation administration of patient, standardize waiting times, as well as add facilities at the nurse station and improve the quality of the information system to make it better.